2011
DOI: 10.1093/annonc/mdq343
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography/computed tomography in the management of recurrent/metastatic breast cancer: a large retrospective study from the Royal Marsden Hospital

Abstract: PET/CT is useful in accurately staging metastatic disease, assessing response to systemic treatment and clarifying equivocation on other imaging. Incorporation of PET/CT in these areas contributes to breast cancer management optimisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 24 publications
2
33
0
2
Order By: Relevance
“…In addition, our results agree with that of Constantinidou A et al [23] stating that PET/CT is equally specific and more sensitive than other imaging modalities in detecting small lesions (5-10 mm), particularly lymph nodes as well as visceral and bone disease. A significant proportion of their patients had PET/CT scans for staging in the recurrent and metastatic disease, especially in cases of rising tumor markers.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our results agree with that of Constantinidou A et al [23] stating that PET/CT is equally specific and more sensitive than other imaging modalities in detecting small lesions (5-10 mm), particularly lymph nodes as well as visceral and bone disease. A significant proportion of their patients had PET/CT scans for staging in the recurrent and metastatic disease, especially in cases of rising tumor markers.…”
Section: Discussionsupporting
confidence: 92%
“…PET/CT outperformed PET alone and conventional imaging but not MRI. Compared with conventional imaging, PET/CT provides better prognostic stratification by discriminating patients with locoregional recurrence only from those with distant recurrence (30,34,35) and is helpful for downstaging suspected lesions in some situations (34,50).…”
Section: Pet/ct In Restaging Of Breast Carcinomamentioning
confidence: 99%
“…Conventional morphological imaging often yields equivocal or negative findings when trying to iden-tify sites of breast cancer recurrence. However, various studies originating from centres that perform serial CA15-3 measurements as part of routine surveillance in breast carcinoma patients have shown that FDG PET/CT imaging can complement information provided by morphological imaging techniques, increasing both sensitivity and specificity for recurrence detection of breast cancer [23][24][25][26][27][28][29][30][31]. These studies have been recently the subject of a metaanalysis.…”
Section: Breast Cancermentioning
confidence: 99%
“…Impor-tantly, for CA15-3 driven prescription of FDG/PET/CT imaging, a CA15-3 cut-off level, either of a single value or of a percentage increase over time, allowing identification of those patients likely to present with FDG PET/CT positive findings would be of great clinical interest. How-ever, while in breast cancer patients suspected to suffer from disease recurrence CA15-3 levels as well as increases of CA15-3 levels over time have proven systematically higher in PET positive patients when compared to PET negative patients, no single cut-off value yielding an acceptable sensitivity and specificity has been identified for either variable [23][24][25][26][27][28][29][30][31][32]. Rather the combination of increases in CA15-3 over time and the clinical suspicion of progression should prompt clinicians to perform PET/CT imaging.…”
Section: Breast Cancermentioning
confidence: 99%